2021
DOI: 10.1111/1755-6724.14883
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Fracturing‐induced Seismicity at the Hot Dry Rock Site of the Gonghe Basin in China

Abstract: Hot dry rock is becoming an important clean energy source. Enhanced geothermal systems (EGS) hold great promise for the potential to make a contribution to the energy inventory. However, one controversial issue associated with EGS is the impact of induced seismicity. In August 2019, a hydraulic stimulation experiment took place at the hot dry rock site of the Gonghe Basin in Qinghai, China. Earthquakes of different magnitudes of 2 or less occurred during the hydraulic stimulation. Correlations between hydrauli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Improving permeability and promoting the efficient circulation of oil and gas mandate the injection of highpressure fluids into the reservoir through hydraulic fracturing technology to create or expand fracture networks [6,7]. The emergence of fractures is accompanied by the occurrence of numerous microseismic events (M L < 3), typically imperceptible to human, and occasionally capable of initiating larger induced earthquakes [8][9][10]. Ensuring the effectiveness and safety of hydraulic fracturing mandates the installation of detectors either on the surface or downhole to monitor the fracturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Improving permeability and promoting the efficient circulation of oil and gas mandate the injection of highpressure fluids into the reservoir through hydraulic fracturing technology to create or expand fracture networks [6,7]. The emergence of fractures is accompanied by the occurrence of numerous microseismic events (M L < 3), typically imperceptible to human, and occasionally capable of initiating larger induced earthquakes [8][9][10]. Ensuring the effectiveness and safety of hydraulic fracturing mandates the installation of detectors either on the surface or downhole to monitor the fracturing process.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the fow-back fuid is typically harmful to the environment, making its handling difcult and costly. In addition, recent research showed large-scale multistage hydraulic fracturing will generate microseismic [1], which may further trigger stronger geological movements and be a serious threat to people's lives and properties. China is a country with scarce water resources per capita, and the distribution of water resources is uneven.…”
Section: Introductionmentioning
confidence: 99%